Students’ Need Analysis Of English Subject At Elementary School In Kabupaten Lima Puluh Kota - Dwi Settya Mahaputri (Al Bahri: Journal of Islamic Education, 2024)
Need analysis is a specific ground for finding information about learners basic needs in accordance with the priority of learning a particular language to develop students’ knowledge and skills in language learning. This research aims to investigate students’ need on English subject at Elementary school in Kabupaten Lima Puluh Kota. The researcher used descriptive qualitative method. The research subject are the teachers and parents from grade 4and 5 at elementary school students’. A set of questionnaire and interview are distributed to get the data. In analyzing the data, the researcher used the steps, there are: data managing, reading/memoing, classifying, interpreting and writing report. The findings indicate that 91,26% of the participant agree that is needed to be taught English subject at elementary school in Kabupaten Lima Puluh Kota. While 97,57% of the teachers stated that target need is needed to teach English subject at elementary school and 86,55% of the teachers stated that learning need is needed to teach English subject at elementary school. Supported by the result of interview with the teachers, the researcher found that target need is necessary to teach English subjet at elementary school to continue students in junior high school later. The teachers stated that learning need is needed to be taught vocabulary with English basic material such as alphabet, objects, part of body and colors. The teachers also stated that it is necessary using interested strategy such as games and medias, for example pictures, guessing pictures and puzzle. Then the researcher found 94,52% of the parents stated that target need is needed to teach English subject at elementary school and 86,41% stated that learning need is needed to teach English subject at elementary school.